Promoting Justice in the Classroom: Looking Beyond the Label to See the Individual. Issue 2 (3rd May 2016) - Bonner, Robert
ABSTRACT: Christian educators are faced with the task of promoting and encouraging justice from the viewpoint of Christ as they encounter the broad strokes of diversity within their classrooms and schools. Following Christ means that the Christian educator must look beyond the labels that have been applied by the religious and secular to see each student as made in the image of God. This article presents a paradigm that recognizes the worth of each individual within the context of the student's background knowledge, language abilities, academic achievement, and behavior (BLAB) instead of the singularly focused labels that marginalize students.